Answer :

Hrishii

Step-by-step explanation:

[tex]y - 2x = 6 ...(1)\\ \\ y + 2x = 0...(2) \\ adding \: equations \: (1) \: and \: (2) \\ \\ y - 2x = 6 \\ y + 2x = 0 \\ - - - - - \\ 2y = 6 \\ \therefore \: y = \frac{6}{2} \\ \huge \red{ \boxed{\therefore \: y = 3}} \\ substituting \: y = 3 \: in \: equation \: (2) \\ \therefore \: 3 + 2x = 0 \\ \therefore \: 2x = - 3 \\ \therefore \: x = \frac{- 3}{2} \\ \huge \orange{ \boxed{\therefore \: x = - 1.5}} \\ [/tex]

Answer:

y = 3, x = -3/2

Step-by-step explanation:

y - 2x = 6 ........ equation 1

+ y + 2x = 0 ......... equation 2

_________

2y + 0 = 6

2y = 6

y = 6/2

y = 3

Sub for y in equation 1

y - 2x = 6

3 - 2x = 6

Collect like terms

-2x = 6 - 3

-2x = 3

x = 3/-2

x = -3/2

Therefore y = 3, x = -3/2

Other Questions